2020
DOI: 10.1108/ijdrbe-06-2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Guiding factors for planning public open spaces to enhance coastal cities’ disaster resilience to tsunamis

Abstract: Purpose Public open spaces (POS) in cities are often measured as a strength to enhance cities’ sustainability with a contribution to the three pillars: economic, social and environmental. Nevertheless, the importance of POS for disaster resilience is less recognised and remains under-rehearsed in the urban planning context. Within this context, this research paper aims to investigate the methods and approaches of using POS to enhance the coastal cities’ resilience to tsunamis through planning and designing int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Following the 2015 earthquake, substantial evidence proves the claim that KMC has experienced the rise or increase in number of new POSs.The development and expansion of new POS were initiated or enhanced by KMC to address the evacuation of encroached land, expand river corridors, and conserve POS within KMC. After the 2015 earthquake, there is evidence supporting this argument that KMC has witnessed the emergence of new POSs for disaster risk reduction and other social implications in many ways (see Mishra, 2004;Jayakody & Amarayhunga, 2016;Saxena, 2016;Jayakody et al, 2018 (Sapkota, 2080). The emergence of these public open spaces can be viewed as a response to the post-disaster realization of the importance of POS for DRRM and public use.…”
Section: Kathmandu Witnessed the Rise Of Pos After The Disastermentioning
confidence: 99%
“…Following the 2015 earthquake, substantial evidence proves the claim that KMC has experienced the rise or increase in number of new POSs.The development and expansion of new POS were initiated or enhanced by KMC to address the evacuation of encroached land, expand river corridors, and conserve POS within KMC. After the 2015 earthquake, there is evidence supporting this argument that KMC has witnessed the emergence of new POSs for disaster risk reduction and other social implications in many ways (see Mishra, 2004;Jayakody & Amarayhunga, 2016;Saxena, 2016;Jayakody et al, 2018 (Sapkota, 2080). The emergence of these public open spaces can be viewed as a response to the post-disaster realization of the importance of POS for DRRM and public use.…”
Section: Kathmandu Witnessed the Rise Of Pos After The Disastermentioning
confidence: 99%
“…The review has shown that there are a great many actors who are involved in the planning and decision-making process of resilience through/of urban form. These actors have different perspectives and priorities and include, for example: urban/town planners [89,103,104,114,115,117,[124][125][126][127][128][129], policymakers [89,99,104,114,117,124], urban designers [30,75,89,104,127], decisionmakers [98,103,125,128,130], architects [75,115], researchers [99], urban managers [114], coastal planners [126], landscape designers [75], politicians [117] and sociologists [126].…”
Section: Who Determines Resilience?mentioning
confidence: 99%
“…Most of the research carried out in the reviewed literature focused on the resilienc of the general population, where terms such as society [99,117,[131][132][133][134][135][136][137][138][139][140][141][142][143], city residen [89,91,94,[144][145][146][147], community [77,98,148], ecosystem [137,149] and stakeholders [98,150 were recurrent. Examples of the specified population that was addressed in a few of th reviewed publications include: the low-income population in Accra, Ghana [116]; the M durese migrants in Indonesia [112]; African Americans in the US [115]; the tsunami-a fected communities in Sri Lanka [126]; and the local residents of Nablus, Palestine [120] 3.2.5. Pathways to Urban Resilience Figure 5 shows that 38 out of 106 of the reviewed publications focused on the adap ability pathway to resilience, 33 focused on persistence, 18 did not take an explicit positio (or are unclear), nine discussed a combination of pathways and eight focused on tran formability.…”
Section: Resilience For Whom?mentioning
confidence: 99%
“…Furthermore, they state that different open space typologies contribute to different functions from the field to the park. Therefore, it is crucial to consider their connectivity through the road network [4].…”
Section: Introductionmentioning
confidence: 99%
“…Open spaces in disaster-prone areas serve as evacuation sites. Open space is vital in mitigation strategies for public open spaces to make cities resilient to disasters [4] [5]. Based on the Ministerial Decree [6].…”
Section: Introductionmentioning
confidence: 99%